Advances in Industrial and Production Engineering Select Proceedings of FLAME 2018 - Shanker, Kripa; Shankar, Ravi.; Sindhwani, Rahul; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprises select proceedings of the International Conference on Future Learning Aspects of Mechanical Engineering (FLAME 2018). The book discusses different topics of industrial and production engineering such as sustainable manufacturing systems, computer-aided engineering, rapid prototyping, manufacturing management and automation, metrology, manufacturing process optimization, casting, welding, machining, and machine tools. The contents of this book will be useful for researchers as well as professionals. .
Enhanced Fluorescence Based Detection of Vibrio Cells Over Nanoporous Silica Substrate -- Wear Analysis of Al-5083 Alloy Reinforced With Chromium Oxide Filler on Air Jet Erosion Test Rig -- Statistical Analysis of Surface Roughness Using Rsm In Hard Turning of Aisi 4340 Steel With Ceramic Tool -- Parametric Investigation Into Alumina Nano Powder Mixed Edm of Inconel 825 Alloy Using Rsm -- Eco Design Approaches For Developing Eco-Friendly Products: A Review -- Plumbene: A New 2d-Material Resembling Grapheme -- Study the Wear Behaviour Of Al5083-7% B4c Composite Fabricated By Stir Cast Technique -- Study of Machining Performance in Edm Through Response Surface Methodology -- Friction Stir Welding of Thermoplastic Composites -- Numerical Simulation of Temperature Distribution Welding of Aisi 316 -- A Framework for Flexible Job Shop Scheduling Problem Using Simulation-Based Cuckoo Search Optimization -- An Experimental Study to Evaluate the Warpage and Cracking Issues in Fused Deposition Modeling -- Optimization of Electrical Discharge Boron Carbide as Reinforcements.-Weld Strength Analysis of Ultrasonic Polymer Welding Using Adaptive Neuro-Fuzzy Inference System -- A Brief Review on Different Lubricants Used in Mql Effects of Welding Parameters in Friction Stir Welding of Stainless Steel and Aluminum -- Process During Hard Turning -- Applicability of Lean Six Sigma in Hospitals.
Keywords: Manufactures; Multibody systems; Vibration; Mechanics, Applied; Control engineering; Robotics; Automation; Machines, Tools, Processes; Multibody Systems and Mechanical Vibrations; Control, Robotics, Automation